2015
DOI: 10.1371/journal.pone.0132609
|View full text |Cite
|
Sign up to set email alerts
|

Coaxial Electrospray of Curcumin-Loaded Microparticles for Sustained Drug Release

Abstract: Curcumin exhibits superior anti-inflammatory, antiseptic and analgesic activities without significant side effects. However, clinical dissemination of this natural medicine is limited by its low solubility and poor bio-availability. To overcome this limitation, we propose to encapsulate curcumin in poly(lactic-co-glycolic acid) (PLGA) microparticles (MPs) by an improved coaxial electrospray (CES) process. This process is able to generate a stable cone-jet mode in a wide range of operation parameters in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 27 publications
0
63
0
Order By: Relevance
“…Recently, we succeeded in preparing artemether-loaded and curcumin-loaded core-shell-structured PLGA MPs using CEHDA process for different applications in our lab [23,34]. However, in the present study, we have developed CEHDA technology for scalable production of PTX-laden SLMPs (PTX-SLMPs) with core-shell structure in a single-step process.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, we succeeded in preparing artemether-loaded and curcumin-loaded core-shell-structured PLGA MPs using CEHDA process for different applications in our lab [23,34]. However, in the present study, we have developed CEHDA technology for scalable production of PTX-laden SLMPs (PTX-SLMPs) with core-shell structure in a single-step process.…”
Section: Introductionmentioning
confidence: 92%
“…Several delivery systems, including mono-disperse Taxol-loaded poly-caprolactone (PCL) MPs, are fabricated using single axial electrospray with high encapsulation efficiency [22]. This process is able to produce particles in a single step, but the resultant drug release profile is suboptimal due to the lack of a core-shell structure [23]. The coaxial electro hydrodynamic atomization (CEHDA) process has the ability to overcome this limitation by producing multilayer microparticles with a core-shell structure [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting material avoids complications with protein dispersion throughout a polymer matrix by localizing protein within the interior of the structure (Zamani, Prabhakaran, Thian, & Ramakrishna, 2014). Controlling the flow rate of both the fluids is essential in the successful formation of the core-shell structure and the thickness of the polymer shell can be tuned via the flow rate of the polymer phase (Jiang et al, 2005;Yuan et al, 2015). The polymer concentration and molecular weight are also important parameters due to the influence on the solution viscoelastic properties (Ramachandran et al, 2017).…”
Section: Electrospinning and Electrosprayingmentioning
confidence: 99%
“…Yuan et al reported a CES system consisting of a droplet generation module, a droplet collection module, and a process monitoring module [17]. The droplet generation module included a coaxial needle made of an inner needle and an outer needle.…”
Section: Bilayered Core-shell Plga Microspheresmentioning
confidence: 99%